IMPLEMENTASI FUZZY LOGIC CONTROLLER - MCS 51 UNTUK PENGATURAN TEMPERATUR RUANG DAN PUTARAN MOTOR DC - Roswaldi Sk; H A Mooduto (Jurnal Teknik Mesin, 2004)
In this research is method implementation conduct logic fuzzy - MCS 51 and used for roomtemperature arrangement and DC motor rotation were applied Incubator Baby machine. The research desired room temperature arrangement used to heater element and motor rotation arrangement as stabilize room temperature. The condition is wanted in this research is although trouble at fickle burden, but room temperature stability remain to earn to be defended according to desire. Advantages are system will become more stable, this will seen at respond of yielded output as well as system resilience to trouble. With easier system controller logic fuzzy to be adapted for various condition of yielding reliable and stable control system